Io Moth Automeris io (Fabricius) (Insecta: Lepidoptera: Saturniidae) - Donald W. Hall (EDIS)
The beautiful Io moth is one of our most recognizable moths, because of its prominent hind wing eyespots. The attractive Io moth caterpillar is also well-known because of its painful sting. But like many of the other saturniid moths, is less common now in parts of its range. With the exception of Cape Cod and some of the Massachusetts islands, it is now rare in New England where it was once common, and its populations have declined in most of the Gulf States since the 1970s. This 12-page fact sheet was written by Donald W. Hall, and published by the UF Department of Entomology and Nematology, December 2014. (Photo: Donald W. Hall, UF/IFAS)